Essential role of mitochondrial Stat3 in p38MAPK mediated apoptosis under oxidative stress - Cheng, Xinlai; Peuckert, Christiane; Wölfl, Stefan (Scientific reports, 2017)
Stat3 is an oncogene, frequently associated with malignant transformation. A body of evidence implicates that phospho-Stat3Y705 contributes to its nucleic translocation, while phospho-Stat3S727 leads to the accumulation in mitochondria. Both are of importance for tumor cell proliferation. In comparison to well-characterized signaling pathways interplaying with Stat3Y705, little is known about Stat3S727. In this work, we studied the influence of Stat3 deficiency on the viability of cells exposed to H2O2 or hypoxia using siRNA and CRISPR/Cas9 genome-editing. We found dysregulation of mitochondrial activity, which was associated with excessive ROS formation and reduced mitochondrial membrane potential, and observed a synergistic effect for oxidative stress-mediated apoptosis in Stat3-KD cells or cells carrying Stat3Y705F, but not Stat3S727D, suggesting the importance of functional mitochondrial Stat3 in this context. We also found that ROS-mediated activation of ASK1/p38MAPK was involved and adding antioxidants, p38MAPK inhibitor, or genetic repression of ASK1 could easily rescue the cellular damage. Our finding reveals a new role of mitochondrial Stat3 in preventing ASK1/p38MAPK-mediated apoptosis, wich further support the notion that selective inhibition mitochondrial Stat3 could provide a primsing target for chemotherapy.